Age model data from IODP Site 323-U1340 - Kimberly deLong; Terrence Blackburn; Beth Caissie; Jason A Addison; Zuzanna N Stroynowski; Maria Reimi Sipala; Franco Marcantonio; Ana Christina Ravelo (PANGAEA, 2025)
The Bølling-Allerød deglacial event is marked by high diatom productivity and opal deposition throughout the subarctic Pacific. To investigate the cause of this event, we quantified several productivity-related sedimentary parameters that reflect the near-surface biogeochemistry from the Integrated Ocean Drilling Program (IODP) Site 323-U1340 in the Bering Sea. We created a new age model for 323-U1340 (53°24N, 179°31W, 1295 m water depth) using previously published radiocarbon data and the occurrence of laminated intervals. All radiocarbon data, originally published in Schlung et al. 2013 (doi:10.1594/PANGAEA.824452 ), were re-calibrated using Calib 8.2 (Stuiver & Reimer, 1993; doi:10.1017/S0033822200013904).